Medium-Term Results of Corticosteroid Injections for Morton's Neuroma. (April 2021) - Hau, Melinda Yun Ting; Thomson, Lauren; Aujla, Randeep; Madhadevan, Devendra; Bhatia, Maneesh
Background: The objective of this study was to evaluate the medium-term results of corticosteroid injections for Morton's neuroma. Methods: This was a prospective follow-up study of a previous randomized controlled trial (RCT). Forty-five neuromas in 36 patients were injected with a single corticosteroid injection either with or without ultrasound guidance. As the results of the RCT showed no difference in outcomes between techniques, the data were pooled for the purpose of this study. Questionnaires were sent out and responses were collected via mail or telephone interview. Results were available in 42 out of 45 neuromas. There was a sex split of 68% female/32% male with a mean age of 62.6 years (SD, 12 years). Results: At mean follow-up of 4.8 years (SD, 0.91 years), the original corticosteroid injection remained effective in 36% ( n = 16) of the patients. In these cases, the visual analog scale (VAS) pain score ( P < .001) and Manchester-Oxford Foot Questionnaire Index (MOxFQ Index) ( P = .001) remained significantly better than preintervention scores. The remaining cases underwent either a further injection or surgery. Fifty-five percent of the 11 neuromas that received a second injection continued to be asymptomatic in the medium term. Overall, 44% ( n = 20) of the initial cohort underwent surgical excision by the medium-term follow-up. The VAS score, MOxFQ Index, and satisfaction scale score across all groups were not significantly different. Conclusion: Corticosteroid injections for Morton's neuroma remained effective in over a third of cases for up to almost 5 years. A positive outcome at 1 year following a corticosteroid injection was reasonably predictive of a prolonged effect from the injection. Level of Evidence: Level II, prospective comparative study.